Enhancing Anterior Esthetics with the Abram’s Roll Technique: A Clinical Case Report - Maharjan, Sanish; KC, Smriti; Dhyako, Niraj; Marattha, Pratik (Journal of Nepalese Prosthodontic Society, 2026)
The maxillary anterior region presents challenges in prosthetic rehabilitation due to its high aesthetic demand and the crucial function of the soft tissues. Among various soft tissue augmentation procedures, Abrams’s roll technique has been widely used in the maxillary anterior region where aesthetics is a prime concern. This case report entails the prosthetic rehabilitation of missing maxillary right and left central incisors with conventional porcelain fused to metal fixed partial denture. The esthetic enhancement was analyzed with digital smile design, and facilitated by the ovate pontic site development with the help of Abram’s roll technique which was also used for the correction of Seibert’s Class I ridge defect. The soft tissue augmentation procedure can be used as a valuable and predictable aid for enhancing the esthetic outcome in conventional fixed partial denture in maxillary anterior teeth region.